SMART CLOTHESLINE: ARDUINO-CONTROLLED DRYING SYSTEM WITH LIGHT AND RAIN DETECTION - Hasbi, Putranugra; Ryan, Agung; Rumapea, Elsa Sri Erjuni; Pane, Amirah Nova Khairiyah; Maulidina, Siti Nur (JURNAL LOGISTICA, 2025)
Unpredictable weather changes often complicate the process of drying clothes, especially when sudden rainfall occurs. To address this issue, an automatic clothes drying system was designed based on the Arduino Uno microcontroller, utilizing a Light Dependent Resistor (LDR) sensor and a rain sensor. The LDR sensor detects sunlight intensity, while the rain sensor identifies the presence of rain. When sufficient sunlight is detected and no rain is present, the system activates a DC motor to automatically extend the clothesline. Conversely, if rain is detected or sunlight intensity decreases, the DC motor retracts the clothesline into a sheltered area. The objectives of this research are to (1) Protect clothes from getting wet due to sudden rainfall; (2) Optimize the drying process by utilizing sunlight intensity; (3) Reduce manual intervention in the drying process, providing convenience for users who are frequently away from home. System testing demonstrated that the device effectively responds to weather changes, thereby protecting clothes from rain and maximizing drying during sunny conditions. This system offers a practical solution for users concerned about the state of their laundry when they are not at home.